50 WATTS HPL LIGHT INTENSITY BASED ON FORWARD CURRENT AS A BASIS IN CONSTRUCTION DESIGN OF FISH ATTRACTOR DEVICE - Sumardi Sadi (Jurnal Teknik, 2018)
The use of HPL (High Power LED) lamps for fish attractor device on capture fisheries will experience difficulties if the light intensity were not known yet. Light characteristics of 50 Watts HPL are the intensity of HPL with Lux units. The intensity of 50 Watts HPL light determine the shape and structure of the device which is designed as fish attractor device. Tools and materials which used in this light intensity test were using Voltage Regulator, LED Driver, Volt meter, Ammeter (Ampere meter), Resistor and Lux meter. The methodology was an experiment in the laboratory. LED direct test were using a measuring instrument and one-way direction (direct) current source. The procedure conducted by installation of measuring instruments and the provision of direct electric current on HPL. The measurement resulted light intensity on red, green and blue HPL. Red HPL had light intensity of 233 Lux at 0.50 Amps current, green HPL had light intensity of 142 Lux at 0,20 Amps current and blue HPL had light intensity of 86 Lux at 0,20 Amps current. The combined color of red, green, and blue HPL had light intensity of 197 Lux at 0.50 Amps current.Keyword: HPL, Light Intensity, Ampere, Lux, Capture Fisheries.